Hubungan Tingkat Pengetahuan Remaja dan Cara Pencegahan Tentang Penyakit Hepatitis A - Taufiqur Rahman; Firdawsyi Nuzula; Siswoto Hadi Prayitno (Jurnal Ilmiah Kesehatan Rustida, 2021)
Hepatitis is a public health problem in developing countries, one of which is Indonesia. Hepatitis A attacks the liver because Hepatitis A virus infection can be caused by a virus. Pukesmas Sumbersari recorded the highest number of Hepatitis A patients with 79 cases in Jember Regency. This study aims to determine the relationship between the level of knowledge of adolescents about Hepatitis A and Hepatitis A prevention methods in the village of Sumbersari, Jember Regency. Design of this study used quantitative methods with descriptive correlation analysis design with cross sectional approach. The population in this study was the adolescent village of Sumbersari, Jember Regency as many as 57 populations. The sampling technique used was Simple Random Sampling. The statistical test used was Chi-Square with a significant standard (< 0.05). Based on the bivariate analysis using the Chi-Square statistical test , it was found that the significant level of value ( ρ) was 0.026 because ( ρ ): 0.026 < α 0.05, then Ha was accepted, meaning that there was a relationship between the level of knowledge of adolescents about hepatitis A and how to prevent hepatitis A in the village. Sumbersari Jember Regency. Based on the results of the study, the adolescents in Sumbersari Village with the knowledge level were mostly moderate, namely 58% and by the prevention method, most of them were good, namely 88%.